2020
DOI: 10.1186/s13071-020-3991-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Rickettsia conorii in artificially contaminated whole and leukoreduced canine blood units during the storage period

Abstract: Background: The ability of tick-borne agents to survive in stored blood bags is a key factor for their transmissibility by blood transfusion. The aim of this study was to evaluate the survival and potential infectivity of Rickettsia conorii (RC) in artificially contaminated canine whole blood (WB) and in leukoreduced whole blood (LR-WB) during the storage period. Methods: RC was cultured on L929 cells. We used a one-week 25-cm 2 flask with 70-80% of L929 infected cells to prepare the bacterial inoculum by pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…16 Prestorage leukoreduction reduces the incidence of FNHTRs in human medicine from 50% to 80%, 32,33,35,36 most likely by abrogating the accumulation of these cytokines. 10 In vitro studies show that leukoreduction is effective in decreasing the levels of IL-6 and IL-8 in canine stored blood, 11,37,38 decreasing the presence of Rickettsia conorii in infected blood units, 39 preventing the release of vascular endothelial growth factor (VEGF) during storage 28 and decreasing procoagulant activity in stored PRBC. 29 In healthy dogs leukoreduction decreases the inflammatory response to transfusion of 21-day old PRBC, 40 measured by white blood cell and segmented neutrophil counts, fibrinogen concentration and C-reactive protein values.…”
Section: Discussionmentioning
confidence: 99%
“…16 Prestorage leukoreduction reduces the incidence of FNHTRs in human medicine from 50% to 80%, 32,33,35,36 most likely by abrogating the accumulation of these cytokines. 10 In vitro studies show that leukoreduction is effective in decreasing the levels of IL-6 and IL-8 in canine stored blood, 11,37,38 decreasing the presence of Rickettsia conorii in infected blood units, 39 preventing the release of vascular endothelial growth factor (VEGF) during storage 28 and decreasing procoagulant activity in stored PRBC. 29 In healthy dogs leukoreduction decreases the inflammatory response to transfusion of 21-day old PRBC, 40 measured by white blood cell and segmented neutrophil counts, fibrinogen concentration and C-reactive protein values.…”
Section: Discussionmentioning
confidence: 99%
“…Haemobartonella canis 146,147 -dog Candidatus Mycoplasma haematoparvum 148 -dog Anaplasma phagocytophilum 192 -dog Rickettsia conorii 193 -dog Bartonella henselae 194,195 -catMycoplasma haemofelis , 196 'Candidatus Mycoplasma haemominutum' 197 -cat…”
Section: Bacteria Virus Parasitementioning
confidence: 99%
“…The risk of transfusion-transmitted Rickettsia is unknown, however, single cases of R. rickettsia and R. parkeri have been described so far 57 , 58 . Lucchese and co-authors 59 have demonstrated that R. conorii was able to remain viable in dog blood stored until 35 days. Therefore further studies about the risk of transfusion-transmitted Rickettsia infection are essential, especially if we take into account that blood recipients are often immunosuppressed 60 .…”
Section: Discussionmentioning
confidence: 99%